2017
DOI: 10.1016/j.kjms.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin‐1β and extracellular signal‐regulated kinase 1/2 in glucose‐stimulated insulin secretion

Abstract: Glucose-stimulated insulin secretion (GSIS) is one of the important physiological characteristics of islet β cells, and extracellular-regulated protein kinase 1/2 (ERK1/2) is an important member of the mitogen-activated protein kinase family that regulates this process. The inflammatory cytokine interleukin (IL)-1β can inhibit the insulin secretion of pancreatic β cells, but the exact mechanism is unclear. This study was designed to investigate the inhibitory effect of IL-1β on GSIS in βTC-6 cells and its rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Our results showed that 1.4 mM glucose had the highest activity in the GSIS of β-TC-6 cells with 1.7-fold higher than the control group (Figure S7A). This result was consistent with a previous study showing that β-TC-6 cells were more sensitive to 1.4 mM glucose …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Our results showed that 1.4 mM glucose had the highest activity in the GSIS of β-TC-6 cells with 1.7-fold higher than the control group (Figure S7A). This result was consistent with a previous study showing that β-TC-6 cells were more sensitive to 1.4 mM glucose …”
Section: Resultssupporting
confidence: 94%
“…β-TC-6 cells (3 × 10 5 cells/mL) were seeded in 24-well plates and allowed to adhere for 48 h. Cells were changed into Krebs-Ringer bicarbonate HEPES buffer (KRBH, Leagene, China) with or without 0.1% bovine serum albumin (BSA) for 30 min. Then, the supernatant was removed and replaced by new assay buffer containing different concentration of glucose (Sigma, USA) and tested chemicals in KRBH buffer (with or without 0.1% BSA) for 60 min . Next, the supernatant of each well was collected into a new tube separately; cells that adhered on the bottom of each well were lysed by RIPA (Solarbio, China) for 20 min and then the cell lysate of each well was collected into another tube.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Weaver et al (36) revealed that GSiS was attenuated by the inflammatory cytokines TNF-α, il-1β and IFN-γ, but protected by the nadPH-1 oxidase-1 inhibitor Ml171 in isolated mouse islets and murine β cell lines. Our previous study found that il-1β and/or IFN-γ inhibited insulin secretion by βTc-6 cells in a glucose stimulation test with a synergistic effect, and the inhibitory effect of il-1β on GSiS was dose-dependent (15). The present study revealed similar results in Min6 cells.…”
Section: Discussionsupporting
confidence: 88%
“…our previous studies showed that the optimal concentration of glucose for the stimulation of βTC-6 cells was 1.38 mmol/l, but the peak value of insulin secretion after stimulation was only 26% higher than the base value (14,15). Min6 pancreatic β cells are more sensitive to glucose than βTc-6 cells in the study of insulin secretion (16).…”
Section: Different Mapk Signal Transduction Pathways Play Different Roles In the Impairment Of Glucose-stimulated Insulin Secretion In Rementioning
confidence: 95%
See 1 more Smart Citation